STUDI PERSEPSI MASYARAKAT MENGENAI DAMPAK PENINGKATAN KUALITAS JALAN TENTENA–TONUSU TERHADAP AKTIVITAS EKONOMI MASYARAKAT DI KECAMATAN PAMONA UTARA KABUPATEN POSO - Saleh, Khairul (Katalogis, 2015)
This research aimed at explaining descriptively about the communities perception of Tentena – Tonusu road quality increasing in accorance with economy activities, mainly on accesibilty, land value and productivity of community in North Pamona Sub-district of Poso Regency. The population of the research is community that live along side of the Tentena – Tonusu road that consist of 495 people, and there is 80 respondent that choosed by using purposive technical sampling. The research type is desctriptive with quantitative approach. Data collected through questionaire, interview and documentation. Data analyzed by percentation analysis. The research result shows that the degree of community accesibility and mobility is increased and influence significantly after the increasing of road. For the increasing acces to interact with another area, so that the utility and value of land at road ring is also increased, 2). The impact of Tentena-Tonusu road quality increasing is influence significantly on the increasing of quantity and quality of agriculture commodity, 3). The increasing of community income in North Pamona sub-district because of the road quality increasing give a significance contribution to the degree of community welfare and then economy growth increasing.